THEORETICAL FOUNDATIONS OF SELF-EDUCATIONAL ACTIVITY OF FUTURE SPECIALISTS IN MEDICAL AND PHARMACEUTICAL FIELDS - Barjadze, Ruslana (European Science, 2025)
The modern development of medical and pharmaceutical education is accompanied by radical changes in approaches to training future healthcare specialists. The growth of professional knowledge, accelerated technological development, and increased quality re